ID044 The Radioactive Seed localization For Impalpable Breast Cancer Conservative Surgery: Meta-Analysis - Hortência de Jesus Ferreira; Maria Elisa C. Martins Rostelato; Carla Daruich de Souza; Lorena Pozzo; Martha Ribeiro (Jornal de Assistência Farmacêutica e Farmacoeconomia)
Introduction